Evaluation of the Proper Tilt Angle for PV Panels in Dukan District - Rashid, PhD student /Shiraz Usman Rashid; سعید, آ.م.د. پاکیزە عزیز سعید (Sulaimani Journal for Humanities, 2025)
With the increasing demand for economical, clean, and renewable energy, the use of solar photovoltaic (PV) systems is growing. The efficiency of PV panels in generating electrical energy depends on many factors, among which the optimum tilt angle is considered one of the most important. The amount of solar radiation falling on PV panels depends on the inclination angle between the panels and the horizontal surface where they are installed. Changing the angles in the study area an average of 12 times per year increases energy output by 20%–25% compared to using fixed panels throughout the year. However, this adjustment cannot always be implemented due to high operational costs. Therefore, it is more practical to set the panels at a fixed angle that aligns with the appropriate surface orientation and latitude to perform well throughout the year. The aim of this study is to identify the optimal tilt angle and orientation of PV panels throughout the year to maximize energy efficiency. The astronomical location of the study area lies between latitudes 35°35′31″ and 36°12′53″ north, and longitudes 45°20′19″ and 44°42′06″ east. The optimum tilt angle for solar panels in the study area is 35.38°, and the best direction to install the panels is towards the south or southwest at this optimal angle.
Keywords: Energy; Tilt Angle; PV Panels; Solar Radiation; Appropriate direction